Visual Identification System for Aedes Detection using Drones - Soares, Henrique; Patrocínio Jr., Zenilton Kleber G. do; Guimarães, Silvio Jamil F. (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI), 2025)
The proliferation of diseases transmitted by the Aedes aegypti mosquito, such as dengue, poses a persistent challenge to public health systems worldwide. Traditional surveillance methods for identifying breeding sites are often laborintensive and limited in scale. This paper introduces VISADE (Visual Identification System for Aedes Detection), a system designed to automate this process through the use of Unmanned Aerial Vehicles (UAVs) and deep learning. By capturing and analyzing aerial imagery, VISADE employs a state-of-the-art object detection model, YOLOv11m, to identify and georeference potential breeding sites like discarded tires, buckets, and water tanks. A key aspect of our methodology is the use of high-resolution images (1200x1200 pixels) to enhance the detection of small objects, a significant challenge in aerial surveys. Our model, trained on a custom dataset collected in urban areas of Minas Gerais, Brazil, achieved a mean Average Precision (mAP@0.5) of 0.934, demonstrating high efficacy in identifying potential breeding sites. VISADE aims to provide public health authorities with an efficient, scalable, and low-cost tool, generating risk maps to direct vector control actions more effectively.